Microbial assessment in a rare Norwegian book collection - Sequeira, Sílvia O. (2024)
Funding Information: This research was funded by the EEA Grant Fund for Bilateral Relations \u201CMicrobiological contamination in cultural heritage settings: shared experiences for better approaches\u201D (FBR_OC2_66_NOVA.ID.FCT). S. Sequeira and E. Pasnak gratefully acknowledge the support by the Portuguese Funda\u00E7\u00E3o para a Ci\u00EAncia e a Tecnologia (FCT/MCTES) through research grants (CEECIND/01474/2018 and UI/BD/153082/2022) and LAQV-REQUIMTE funding (https://doi.org/10.54499/LA/P/0008/2020 ; https://doi.org/10.54499/UIDP/50006/2020; https://doi.org/10.54499/UIDB/50006/2020). This project was supported by FCT/MCTES UIDP/05608/2020 (https://doi.org/10.54499/UIDP/05608/2020) and UIDB/05608/2020 (https://doi.org/10.54499/UIDB/05608/2020). This work was also supported by national funds through FCT/MCTES/FSE/UE, 2023.01366.BD; UI/BD/153746/2022 and CE3C unit UIDB/00329/2020 (https://doi.org/10.54499/UIDB/00329/2020); UI/BD/151431/2021 (https://doi.org/10.54499/UI/BD/151431/2021) and by Instituto Polit\u00E9cnico de Lisboa, national support through IPL/2022/InChildhealth/BI/12M; IPL/IDI&CA2023/FoodAIIEU_ESTeSL; IPL/IDI&CA2023/ASPRisk_ESTeSL; IPL/IDI&CA2023/ARAFSawmills_ESTeSL. This project was also supported by the Polish Minister of Science and Higher Education, under the program \u201CRegional Initiative of Excellence\u201D in 2019\u20132022 (Grant No. 008/RID/2018/19). C. Pinheiro acknowledges the FCT/MCTES support through CEECIND/02598/2017. C. Pinheiro, M. Penetra, I. Silva, and T.Caldeira acknowledge support from UIDB/04449/2020 (https://doi.org/10.54499/UIDB/04449/2020), UIDP/04449/2020 (https://doi.org/10.54499/UIDP/04449/2020), and LA/P/0132/2020 (https://doi.org/10.54499/LA/P/0132/2020). M. Penetra acknowledges the financial support of the project \u201CROADMAP\u2014Research on Antonio De Holanda Miniatures Artistic Production\u201D (PTDC/ART-HIS/0985/2021), financed by Portuguese funds through FCT/MCTES. I. Santos acknowledges financial support to FCT-MCTES within the scope of the project UI/BD/153582/2022. Publisher Copyright: © 2024 by the authors.